Religious Authority and the Qibla Dispute: A Social Fiqh Analysis of the Mosque Conflict - Nasiri , Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
Mosques normatively function as centers of worship, education, and community unification. However, in practice, mosques can also become spaces for internal conflict due to differences in religious views and organizational management. This research begins with a conflict phenomenon that occurred at the Al-Zainab Mosque, triggered by differences in interpretation regarding the delivery of religious commentary and differences of opinion regarding the placement of prayer rows. This study aims to analyze the dynamics of this conflict and reconstruct its resolution from the perspective of Islamic jurisprudence. The research used a qualitative case-study approach, employing observation, interviews, and documentation. The results show that the conflict was not solely caused by differences in Islamic jurisprudence of worship, but also by weak organizational communication, a low understanding of the principles of Islamic jurisprudence (ikhtilaf), and the absence of a participatory deliberation mechanism. From the perspective of Islamic jurisprudence, this conflict is categorized as ikhtilaf Tanawwu' (Tanawwu'), which should be managed with the principles of Tasamuh (tasamuh), deliberation, and an orientation towards the welfare of the community. This research contributes conceptually by designing a framework for mosque conflict fiqh based on the principle of Maqasid Al Syari'ah as a model for conflict resolution in contemporary religious institutions, thereby enriching social fiqh in the context of modern mosque management.